Potassium Silicate Decreases Nickel Induced Oxidative Stress by Improving Nutrients Uptake and Antioxidant Defense System in Sunflower - Khan, Shah Alam; Iftikhar, Hafiz Usman; Korai, Punhoon Khan; Ali, Hammad; Sumia; Mumtaz, Hassan; Zejnullahu, Besim; Shehzad, Shakir; Abazi, Uran (Indus Journal of Bioscience Research, 2025)
Nickel stress reduces nutrient uptake, leading to oxidative stress and inhibiting plant growth and development. There is insufficient research on the detrimental effects of nickel stress on sunflowers. This study aimed to evaluate the effects of potassium silicate at concentrations of 50 and 100 mg L-1 on the morphophysiological, nutritional, and biochemical characteristics of sunflower plants subjected to nickel stress at levels of 100 and 200 mg L-1. This experiment utilized a completely randomized design with a factorial approach, incorporating three biological replications. The nickel stress negatively impacted plant growth parameters, with the most significant effects observed at high nickel concentrations (200 mg L-1). Under significant nickel stress, potassium silicate (K2SiO3) at a concentration of 100 mg L-1 enhanced plant morphophysiological characteristics, while 50 mg L-1 exhibited non-significant variation. The primary reason may be attributed to enhanced total chlorophyll, nitrogen, phosphorus, and potassium uptake from the soil, with increases of 13.33%, 24.04%, 7.40%, and 40.96%, respectively, following the application of K2SiO3 at a concentration of 50 mg L-1 under nickel stress at 200 mg L-1. This may be linked to a reduction in oxidative stress, encompassing electrolyte leakage, malondialdehyde, and hydrogen peroxide by 23.06%, 10%, and 25.38% respectively under nickel stress. The reduction in oxidative stress may result from enhanced antioxidant activities, specifically superoxide dismutase and catalase, which increased by 31.67% and 7.90%, respectively, under nickel stress. The potassium silicate at 50 mg L-1 was considered as best dose in improving plant growth, nutritional, physiological and biochemical aspects of sunflower under severe nickel stress.